Pojam kulturalne intimnosti u djelu Viktora Pelevina (Philological Studies, 2019)
It is the purpose of this essay to examine how the notion of cultural intimacy has been used by modern Russian writers in an attempt to understand the intricate dynamics of irony in its handling of nationalistic ideas. Current and past forms of social organization in Russia are taken as parameters by which writers like Pelevin orient their writing, and their sensitivity to the tension between „collective self-presentation“ and the embarrassing aspects of „collective self-knowledge“ is key to understanding the role similar types of fiction have had in modern Russian literature, and also understanding their role in recording as well as creating certain forms of social behavior.